KONTROVERSI KEDUDUKAN â€˜ASHABAH DALAM HUKUM WARIS ISLAM MENURUT MADZHAB SYIâ€™AH ITSNA â€˜ASYâ€˜ARIYYAH - Asyâ€™ari, A. Hasyim (Asy-Syari’ah, 2014)
In Islamic inheritance law system, ulama agreed on the distribution of waris as an â€˜ashabah, especially among Sunni. However, it is different from the opiÂnions of ulama among Syiâ€™ah Itsna â€˜Asyâ€˜ariyyah which stated that â€˜ashabah is out part from the Islamic inheritance law system. In determining the law, ulama SyiÂâ€™ah Itsna â€˜Asyâ€˜ariyyah refers to the Koran, Hadith, and the consensus of the ulama (ijma), and the thought by different ways and methodologies with Sunni. Ulama Syiâ€™ah Itsna â€˜Asyâ€˜ariyyah has understood â€˜ashabah with their own understanding. They said that â€˜ashabah (the residual) is only given to a group of men from tirkah given to â€˜ashabah al-furudl, they thought that the residual must be returned to all thabaqat certain groups. Therefore, ulama Syiâ€™ah Itsna â€˜Asyâ€˜ariyyah were denying the extance of â€˜ashabah In the Islamic inheritance law system. Based on the issue, this paper try to explain the underÂstanÂding ofÂ ulama Syiâ€™ah Itsna â€˜Asyâ€˜ariyyah in determining the law, especially in field of â€˜ashabah.